2016
DOI: 10.1111/eci.12687
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of renal function upon reperfusion by ex situ controlled oxygenated rewarming

Abstract: BackgroundPost‐transplant function of suboptimal kidney grafts can be improved but not accurately predicted by hypothermic machine perfusion. Therefore, a new concept of ex situ pre‐implantation machine perfusion with controlled rewarming up to subnormothermic temperatures was developed and evaluated.Materials and methodsPorcine kidneys (n = 6/group) were retrieved before or 30 min after cardiac arrest of the donor and subjected to 18 h of static cold storage. In some cases, 90 min of machine‐controlled oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Our model could also be interesting to establish a proper comparison between the current investigations for preservation improvement such as normothermic preservation, either at the end of the preservation or for the whole duration, or slow rewarming. 63,64 Such preclinical evaluation could establish their true benefits and uncover their potential additivity.…”
Section: Because Coagulation Initiates the Generation Of Fviia And Fxamentioning
confidence: 99%
“…Our model could also be interesting to establish a proper comparison between the current investigations for preservation improvement such as normothermic preservation, either at the end of the preservation or for the whole duration, or slow rewarming. 63,64 Such preclinical evaluation could establish their true benefits and uncover their potential additivity.…”
Section: Because Coagulation Initiates the Generation Of Fviia And Fxamentioning
confidence: 99%
“…In the kidney, functional data during perfusion at 20 °C significantly outweighed the weaker predictive power of markers obtained during hypothermic perfusion [ 63 ▪ ] and showed very well correlations with ulterior renal function upon warm reperfusion.…”
Section: Controlled Oxygenated Rewarmingmentioning
confidence: 99%
“…Similarly, an experimental study of NMP on DCD rat hearts demonstrated beneficial effects on recovery of electrical activity and contractility of the myocardial tissue [29]. Controlled oxygenated rewarming (COR) technique combines 30 minutes HMP, 30 minutes slow warming to 20° C, and then 30 minutes of SNMP, and has been applied after similar periods of SCS to both porcine livers and kidneys procured after cardiac death [5, 30]. In simulated reperfusion models, COR kidneys showed better creatinine clearance, decreased expression of inflammatory molecules, decrease endothelial cell activation, and improved tubular cell integrity compared to untreated kidneys.…”
Section: Machine Perfusion: a Platform For Organ Treatmentmentioning
confidence: 99%